Gestión De Crédito Y Su Proceso En La Cobranza De Comercial Delgado De La Ciudad De Babahoyo - Campuzano Vera, Rita del Rocío (2017)
The companies are natural or legal persons obliged or not required to keep accounts, whose activity is to market goods and services offer their products to potential customers in two different forms of payments: cash and credit. Credit has become a vital tool for these businesses as a method to attract a market willing to meet needs such as acquisition of tangible goods and certain services necessary for a good life and have no liquidity to pay cash . The development of this case study was carried out in Comercial Delgado, a natural unipersonal company forced to carry accounting that is dedicated to the distribution of motorized vehicles, general appliances of recognized marks, mattresses, computer equipment and more household articles and office. It is located in the city of Babahoyo, the beginning of its commercial operations was registered according to register of the Chamber of Commerce of the city of Babahoyo on May 30, 1976, becoming this establishment in the oldest dedicated to this activity in this locality. The objective of this research is to know the management that they make when granting loans to clients, using the technique of the interview to obtain information that allows to understand the risks that this type of business has when making "spun" sales as know what are the preventive measures they take in the sales areas at the time of making a sale on credit and the collection process applied for the 2 recovery of the portfolio that allow it to reduce the delinquency rates they currently own and which has led the company to a situation of illiquidity losing its ability to pay. Also investigate external factors that are natural, social, political or economic factors that prevent customers from canceling their credits with punctuality and internal factors such as the absence of credit and collection policies, lack of communication between the different areas and mainly not having sellers and collectors who become the most important part for this type of business